Tissue-Specific GHR Knockout Mice: An Updated Review - Nagarajan, Akash; Srivastava, Hemant; Jablonsky, Joseph; Sun, Liou Y. (Frontiers in Endocrinology, 2020)
Growth Hormone (GH) signaling plays a key role in mediating growth, development, metabolism and lifespan regulation. However, the mechanisms of longevity regulation at the cellular and molecular level are still not well-understood. An important area in the field of GH research is in the development of advanced transgenic systems for conditional expression of GH signaling in a cell type- or tissue-specific manner. There have been many recent studies conducted to examine the effects of tissue specific GHR disruption. This review updates our previous discussions on this topic and summarize recent data on the newly-made tissue-specific GHR-KO mice including intestinal epithelial cells, bone, hematopoietic stem cells, cardiac myocytes and specific brain regions. The data from these new genetically-engineered mice have a significant impact on our understanding of the local GH signaling function.